Combining Photo‐Organo Redox‐ and Enzyme Catalysis Facilitates Asymmetric C‐H Bond Functionalization. Issue 1 (18th December 2018) - Zhang, Wuyuan; Fueyo, Elena Fernandez; Hollmann, Frank; Martin, Laura Leemans; Pesic, Milja; Wardenga, Rainer; Höhne, Matthias; Schmidt, Sandy
Abstract : In this study, we combined photo‐organo redox catalysis and biocatalysis to achieve asymmetric C–H bond functionalization of simple alkane starting materials. The photo‐organo catalyst anthraquinone sulfate (SAS) was employed to oxyfunctionalise alkanes to aldehydes and ketones. We coupled this light‐driven reaction with asymmetric enzymatic functionalisations to yield chiral hydroxynitriles, amines, acyloins and α‐chiral ketones with up to 99 % ee. In addition, we demonstrate functional group interconversion to alcohols, esters and carboxylic acids. The transformations can be performed as concurrent tandem reactions. We identified the degradation of substrates and inhibition of the biocatalysts as limiting factors affecting compatibility, due to reactive oxygen species generated in the photocatalytic step. These incompatibilities were addressed by reaction engineering, such as applying a two‐phase system or temporal and spatial separation of the catalysts. Using a selection of eleven starting alkanes, one photo‐organo catalyst and 8 diverse biocatalysts, we synthesized 26 products and report for the model compounds benzoin and mandelonitrile > 97 % ee at gram scale. Abstract : Joint forces! The combination of a photo‐organo catalyst with 8 diverse biocatalysts achieves asymmetric C–H bond functionalization of simple alkane starting materials to hydroxynitriles, amines, acyloins, α‐chiral ketones, and transformation into alcohols, esters and carboxylic acids.